In-Service Training Framework for Industrial Relations and Training Officer at Malaysian Vocational College - Mohd Azlan Mohammad Hussain, Rafeizah Mohd Zulkifli, Mohd Firdaus Mustaffa Kamal (Tanjung Malim, 2024)
In-Service Training Framework for Industrial Relations and Training Officer at Malaysian Vocational College by Mohd Azlan Mohammad Hussain, Rafeizah Mohd Zulkifli, Mohd Firdaus Mustaffa Kamal